Association between the p53 polymorphisms and cervical cancer risk: an updated meta-analysis - Zhang, Xi-Qin; Bai, Xiao-Hui; Zhang, Hui-Zhen; He, Xiao-Feng (Frontiers in Oncology, 2025)
BackgroundThe association of the p53 rs1042522 and rs17878362 polymorphisms with cervical cancer risk has been reported in several published original studies and meta-analyses. However, the conclusions of these studies were contradictory. Consequently, we conducted an updated meta-analysis to further validate these debates.ObjectiveTo evaluate the association between the p53 rs1042522 and rs17878362 polymorphisms and cervical cancer risk.Materials and MethodsPubMed, Medline, Ovid, Embase, CNKI, and China Wanfang databases were searched. Association was assessed using odds ratio (OR) with 95% confidence interval (CI). Moreover, the false-positive reporting probability (FPRP), Bayesian false-finding probability (BFDP), and Venice criteria were used to assess the credibility of statistically significant association.ResultsA significantly decreased cervical cancer risk was revealed for the p53 rs1042522 polymorphism (Pro/Pro +Arg/Pro vs. Arg/Arg: OR = 0.79, 95% CI = 0.71-0.87; Pro/Pro vs. Arg/Arg: OR = 0.80, 95% CI = 0.70-0.91; Arg/Pro vs. Arg/Arg: OR = 0.78, 95% CI = 0.71-0.86; Pro vs. Arg: OR = 0.87, 95% CI = 0.81-0.93) in overall analysis and several subgroup analyses, such as in Caucasians, Asians, Indians, and so on. However, no significant association was found between the p53 rs17878362 polymorphism and cervical cancer risk. Despite these statistically significant results, reliability analysis using FPRP, BFDP, and Venice criteria deemed all associations “unreliable”.ConclusionsAfter considering the reliability of the results, this study indicates that the p53 rs1042522 polymorphism is not associated with the cervical cancer risk.